2019
DOI: 10.1038/s41598-019-51437-w
|View full text |Cite
|
Sign up to set email alerts
|

Traditional Processed Meat Products Re-designed Towards Inulin-rich Functional Foods Reduce Polyps in Two Colorectal Cancer Animal Models

Abstract: Inulin-rich foods exert a prebiotic effect, as this polysaccharide is able to enhance beneficial colon microbiota populations, giving rise to the in situ production of short-chain fatty acids (SCFAs) such as propionic and butyric acids. These SCFAs are potent preventive agents against colorectal cancer due to their histone deacetylases inhibitory properties, which induce apoptosis in tumor colonocytes. As colorectal cancer is the fourth most common neoplasia in Europe with 28.2 new cases per 100,000 inhabitant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(24 citation statements)
references
References 87 publications
(90 reference statements)
1
18
0
2
Order By: Relevance
“…This change in taxonomical traits were associated with reduced expression of pro-oncogenic miR17-92, protective against CRC [41]. Functional foods such as processed meat fortified with polysaccharide inulin increases the abundance of anti-inflammatory and fiber fermentative Blautia genus which increase SCFAs like propionate and butyrate [42]. This has shown to reduce colonic polyps in experimental rats possibly due to the anti-inflammatory effects.…”
Section: The Influence Of Diet On Gut Microbiome and Colorectal Cancementioning
confidence: 97%
“…This change in taxonomical traits were associated with reduced expression of pro-oncogenic miR17-92, protective against CRC [41]. Functional foods such as processed meat fortified with polysaccharide inulin increases the abundance of anti-inflammatory and fiber fermentative Blautia genus which increase SCFAs like propionate and butyrate [42]. This has shown to reduce colonic polyps in experimental rats possibly due to the anti-inflammatory effects.…”
Section: The Influence Of Diet On Gut Microbiome and Colorectal Cancementioning
confidence: 97%
“…Similarly, this prebiotic, along with the commercial probiotic VSL#3 ® (Sigma-Tau Pharmaceuticals, Gaithersburg, MD, USA) showed extra benefits in C57BL6/J mice, in comparison with the use of VSL#3 ® alone, culminating in a significant reduction in precursor lesions of CRC [ 26 ]. In other new researches on rats developing CRC, either genetically or by induction carcinogens such as AOM/DSS, various prebiotics such as galacto-oligosaccharides derived from lactulose [ 27 ], inulin [ 28 ], phenolic compounds such as anthocyanins and ellagic acid from Myrciaria jaboticaba ((Vell.) O.Berg) seeds [ 29 ], and Djulis ( Chenopodium formosanum ), a native cereal crop [ 30 ], had preventive effects against CRC progression ( Table 2 ).…”
Section: Prebiotics and Crcmentioning
confidence: 99%
“…These nutrients drive the decline or growth of certain bacterial groups depending on the type of prebiotic [ 40 ]. Studies indicated that inulin-rich foods can enhance prominent propionate producers in Bacteroidetes populations, mainly due to a significant increase in the Bacteroidaceae , Porphyromonadaceae , and especially Prevotellacea families [ 28 ]. Inulin also helps to reduce the phylum Firmicutes , primarily due to lower Lachnospiraceae populations.…”
Section: Mechanisms Of Prebiotics In Crc Preventionmentioning
confidence: 99%
See 2 more Smart Citations